Longitudinal Association Between Cognition and Depression in Patients With Late-Life Depression: A Cross-Lagged Design Study - Wu, Zhangying; Zhong, Xiaomei; Peng, Qi; Chen, Ben; Zhang, Min; Zhou, Huarong; Mai, Naikeng; Huang, Xingxiao; Ning, Yuping (Frontiers in Psychiatry, 2021)
Objectives: Although previous studies have extensively confirmed the cross-sectional relationship between cognitive impairment and depression in depressed elderly, the findings of its longitudinal associations are still mixed. The purpose of this study was to explore the two-way causal relationship between depression symptoms and cognition in patients with late-life depression (LLD). Methods: A total of 90 patients with LLD were assessed across two time points (baseline and one-year follow up) on measures of 3 aspects of cognition and depressive symptoms. The data were then fitted to a structural equation model to examine two cross-lagged effects. Results: Depressive symptoms predicted a decline in executive function (β=0.864,p=0.049) but not vice versa. Otherwise, depressive symptoms were predicted by a decline in scores of working memory test(β=-0.406,p=0.023), respectively. None of the relationship between the two is bidirectional. Conclusion: These results provide robust evidence that the relationship between cognition and depressive symptoms is unidirectional. Depressive symptoms may be a risk factor for cognitive decline. The decrease of information processing speed predicts depressive symptoms.